Impacts of Integrated Marketing Communication Strategies Applied for Geographical Indications on Purchasing Behavior - Ayça Kırgız (İşletme Bilimi Dergisi)
The purpose of this study is to raise the awareness for products with geographical indication (GI) which directly influence the development of local and nation-wide economies, marketing of tourism activities and branding of destination and to investigate the integrated marketing communication (IMC) tools applied for realization of selling and the impact of such tools on shopping behavior. In this study, simple linear regression analysis have been used. The data analysis showed that the perceived quality of food products and IMC tools appear to affect purchase behavior in a positive way. But there are only 200 products in Turkey with GI registration despite the high GI potential thereof. This result reveals the fact that despite the rapidly increasing state incentive the GI concept of Turkey is not yet understood fully and its significance is not understood sufficiently. This has revealed the existence of other fundamental problems which are discussed in part of conclusion and recommendation.